Nutritional quality of fermented bran using aspergillus niger with different incubation time - Yani, Sri Sukar; Fadillah, Muhamad Arif; Purwati, Catur Suci; Yakin , Engkus Ainul; Husein, Muhammad (Fakultas Peternakan Universitas Papua, 2024)
This study aims to determine the effect of long fermentation of rice bran using Aspergillus niger fungus on the content of dry matter (BK), crude protein (PK), and crude fiber (SK). This study used a unidirectional pattern Complete Randomized Design (RAL) with four treatments, and each treatment was repeated three times, namely T0: Fermentation of bran using 2.5% Aspergillus niger for 0 days. Q1: Fermentation of bran using 2.5% Aspergillus niger for 3 days. Q2: Fermentation of bran using 2.5% Aspergillus niger for 5 days. Q3: Fermentation of bran using 2.5% Aspergillus niger for 7 days. Fermentation of rice bran with the addition of 5 grams of urea and 20 ml of molasses The results showed that the average value of BK obtained T0: 94.43%, T1: 82.53%, T2: 95.41%, and T3: 88.01%. The average PK value was obtained: T0:13.03%, T1:13.27%, T2:14.12%, and T3:15.27%. The average SK value was obtained: T0:16.64%, T1:16.56%, T2:15.78%, and T3:12.76%. The conclusion obtained from this study is that the fermentation period of 0 to 7 days using Aspergillus niger mushrooms as much as 2.5% has a real effect on dry matter and crude fiber but has no real effect on crude protein content.